Distribution and influencing factors of macrobenthos on three seagrass beds in the intertidal zone of Shandong province, China - Ji, Yinglu; Song, Bo; Xu, Jiangling; Jiang, Shaoyu; Chen, Linlin; Li, Baoquan (Frontiers in Marine Science, 2024)
Introduction The macrobenthos plays a vital role within the ecosystem of seagrass beds, with its characteristics and spatial distribution serving as indicators of the well-being of the seagrass beds. Methods In August 2018, three seagrass beds located in the Yellow River Estuary of Dongying, the west coast of Yantai, and Swan Lake of Weihai, were investigated to compare the ecological influences of seagrass habitat on the benthic environment and macrobenthic community. Within each seagrass bed, porewater, sediment, and macrobenthos were sampled from three separate stations (center of seagrass bed, edge of seagrass bed and bare area). Results and discussion One-way ANOVA showed significant differences (p < 0.05) in environmental factors and macrobenthos species, abundance, biomass and diversity indices among the three seagrass beds. The present data did not show significant impacts on habitat and macrobenthos in the different coverage areas of seagrass beds at the investigated spatial scales, though crustacea and some carnivores were relatively more inclined to inhabit areas with higher seagrass densities. Aquaculture and eutrophication may trigger the loss of seagrass bed habitats, that affects macrobenthic biodiversity, and conservation measures are needed to protect seagrass bed habitats.